2019
DOI: 10.1097/cm9.0000000000000532
|View full text |Cite
|
Sign up to set email alerts
|

Deep neural network-assisted computed tomography diagnosis of metastatic lymph nodes from gastric cancer

Abstract: Background: Artificial intelligence-assisted image recognition technology is currently able to detect the target area of an image and fetch information to make classifications according to target features. This study aimed to use deep neural networks for computed tomography (CT) diagnosis of perigastric metastatic lymph nodes (PGMLNs) to simulate the recognition of lymph nodes by radiologists, and to acquire more accurate identification results. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…(2019) [48] * Preoperative contrast-enhanced CT images within 2 weeks before surgery; histologically confirmed primary invasive breast cancer; SLN biopsy (and ALND); pathologically results after operation confirmed SLN metastasis Neoadjuvant therapy before CT examination and surgery; poor visualization of the tumor for segmentation due to serious artifacts caused by metallic foreign bodies on the breast; tumor was too small to be seen on CT images; incomplete clinicopathological data 348/348 Training set:184/184 Testing set:164/164 Training set:71(71)/113(113) Testing set:63(63)/101(101) Training set: SLN-P:52(9;NR); SLN—N:50(11;NR) Testing set: SLN-P:50(10;NR); SLN—N:53(10;NR) NR Yuan Gao et al. (2019) [49] NR No metastatic LNs revealed by CT; with preoperative neoadjuvant radio-chemotherapy; complicated with abdominal infection; pathological grouping different from CT grouping; LN adhesions 602/38,495 NR 62(NR;20–91) 72% David Coronado-Gutierrez et al. (2019) [50] * Positive metastatic nodes by ultrasound-guided FNA or CNB; Negative metastatic nodes determined by histopathology Surgical biopsy showed positive result after not suspicious nodes in ultrasound exam or negative results of ultrasound-guided FNA or CNB; Patients refused to receive SLNB 127/118 NR(53)/NR(65) 54.6 (NR;26~91) NR Yukinori Okada et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2019) [48] * Preoperative contrast-enhanced CT images within 2 weeks before surgery; histologically confirmed primary invasive breast cancer; SLN biopsy (and ALND); pathologically results after operation confirmed SLN metastasis Neoadjuvant therapy before CT examination and surgery; poor visualization of the tumor for segmentation due to serious artifacts caused by metallic foreign bodies on the breast; tumor was too small to be seen on CT images; incomplete clinicopathological data 348/348 Training set:184/184 Testing set:164/164 Training set:71(71)/113(113) Testing set:63(63)/101(101) Training set: SLN-P:52(9;NR); SLN—N:50(11;NR) Testing set: SLN-P:50(10;NR); SLN—N:53(10;NR) NR Yuan Gao et al. (2019) [49] NR No metastatic LNs revealed by CT; with preoperative neoadjuvant radio-chemotherapy; complicated with abdominal infection; pathological grouping different from CT grouping; LN adhesions 602/38,495 NR 62(NR;20–91) 72% David Coronado-Gutierrez et al. (2019) [50] * Positive metastatic nodes by ultrasound-guided FNA or CNB; Negative metastatic nodes determined by histopathology Surgical biopsy showed positive result after not suspicious nodes in ultrasound exam or negative results of ultrasound-guided FNA or CNB; Patients refused to receive SLNB 127/118 NR(53)/NR(65) 54.6 (NR;26~91) NR Yukinori Okada et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2019) [48] * LNM SLNM in Breast Cancer Breast cancer Histopathology Resampling method NO Yuan Gao et al. (2019) [49] LNM PGMLNs in GC GC Histopathology; expert consensus Resampling method NO David Coronado-Gutierrez et al. (2019) [50] * LNM Metastasis in the axillary lymph node Breast cancer Histopathology Resampling method NO Yukinori Okada et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AI-assisted endoscopic diagnosis included the extraction of image features[ 7 , 8 ], the detection of early gastric cancer[ 9 - 14 ], the detection of precancerous conditions[ 15 ], the optimization of magnifying endoscopy with narrow-band imaging (M-NBI)[ 16 - 19 ] and the application of Raman endoscopy[ 20 , 21 ]. AI-assisted pathologic diagnosis involved the automatic identification of gastric cancer[ 22 ], the detection of gastric cancer based on the whole slide imaging (WSI)[ 23 - 26 ], the automatic detection of tumor-infiltrating lymphocytes (TILs)[ 27 ] and the segmentation of lesion regions[ 28 - 31 ], while AI-assisted CT diagnosis focused on the identification of preoperative peritoneal metastasis[ 32 ], the detection of perigastric metastatic lymph nodes[ 33 ] and two other new imaging techniques[ 34 , 35 ]. Under certain conditions, the diagnostic performance of these AI models was not inferior to human experts.…”
Section: Ai In the Diagnosis Of Gastric Cancermentioning
confidence: 99%
“…Compared to the current status of poor CT depiction in lymph node metastasis and low detection sensitivity, the novel DL-based model was expected to obtain an excellent performance of CT imaging. Gao et al[ 33 ] developed and validated faster region-based CNN based on CT images. The experimental results showed that faster region-based CNN obtained a high accuracy for the diagnosis of perigastric metastatic lymph nodes with the mean average precision value of 0.7801 and AUC value of 0.9541.…”
Section: Ai In the Diagnosis Of Gastric Cancermentioning
confidence: 99%